Whole-Genome Sequencing of KMR3 and Oryza rufipogon-Derived Introgression Line IL50-13 (Chinsurah Nona 2/Gosaba 6) Identifies Candidate Genes for High Yield and Salinity Tolerance in Rice - Thummala, Shashi Rekha; Guttikonda, Haritha; Tiwari, Shrish; Ramanan, Rajeshwari; Baisakh, Niranjan; Neelamraju, Sarla; Mangrauthia, Satendra K. (Frontiers in Plant Science, 2022)
Whole genome sequencing of the rice restorer line KMR3 and one of its high-yielding introgression lines IL50-13 (Chinsurah Nona 2/ Gosaba 6 derived from KMR3 x Oryza rufipgon BC4), for high-yield in coastal saline areas of West Bengal, India identified polymorphic SNPs and InDels unique and common to both the genomes. Functional enrichment analysis of genes with unique InDels identified GO terms involved in protein ubiquitination, peroxidase and antioxidant activity in IL50-13. KEGG pathway enrichment analysis identified linoleic acid metabolism and circadian rhythm pathways in IL50-13. These GO terms and pathways are involved in reducing oxidative damage. Sequence analysis of QTL markers / genes associated with grain yield both at the seedling and flowering stages in salt tolerant plants showed polymorphism in 20 genes, out of which nine are newly reported for biotic or abiotic stress tolerance in rice. These candidate genes are similar to NB-ARC domain containing protein (Os11g0606800), similar to cyclase (Os02g0187100), similar to receptor-like kinase (Os02g0194400), topoisomerase II-associated protein PAT1 domain containing protein (Os02g0294700), ion channel regulatory protein, UNC-93 domain containing protein (Os12g0566800), subunit A of the heteromeric ATP-citrate lyase (Os12g0566300) and three conserved hypothetical genes. Based on these analyses, polymorphism was observed in the coding, intron and untranslated regions of the genes on chromosome 1, 2, 4, 7, 11 and 12. Genes showing polymorphism between the two genomes (KMR3 and IL50-13) are considered as sequence-based new candidates to verify their role in conferring high yield in Gosaba 6 (IL50-13), a popular stress tolerant rice variety of coastal West Bengal, India.